Contribution to the study of climate changes in Piedmont - ACQUAOTTA, FIORELLA; FRATIANNI, SIMONA (Volume degli abstracts, 2008)
In this report, we have studied the daily thermo - pluviometric series of 21 meteorological stations in Piedmont. The meteorological stations, belonging to ex-SIMN (Hydrographic and Marigraphic National Service), have been operating with continuity during 56 years, from 1951 to 2006. In order to correctly study the climatic variability, we must have at our disposal some homogeneous series (PETERSON et al., 1998). Then we have reconstructed the monthly series and we have applied the homogeneity test SNHT (ALEXANDERSSON et al., 1997) for creating a serially complete (no missing data). This method have afforded to estimate the real trend on every series. Consecutively we have determined and quantify their correlation with large-scale atmospheric pattern and global indices such as the North Atlantic Oscillation (NAO). Finally, to illustrate the trend of temperature and precipitations extreme values, the indices proposed by “CCL/CLIVAR Working Group on Climate Change Detection” have been calculated over WMO 30-year periods (1951-80, 1961-90, 1971-2000). In order to better understand the consequences of climate variations on our society, we have calculated the climatic indexes (frost days, days with no thaw, tropical days, rainy days, density of precipitations) over the whole period and also the use of thermograms, pluviometric regimes, and ombrothermal diagrams underlined differences among the three 30-year periods. The values of temperature and precipitations have also allowed to begin the climatic analysis with the aim at defining the principle local climates in Piedmont, during the period 1951-2006.